Determination of the work resource of synthetic filters for oil diesel systems (Transport systems and technologies, 2019)
In clause questions which are connected with an opportunity of use of synthetic filtering elements in oil systems of diesel locomotives, and also by definition of their resource of work in operation are considered. It is analyzed domestic and foreign researches on use in filtering systems of new porous materials. Thus it is established, that use of such materials causes a lot of problems which are connected with a complex, chaotic arrangement times spaces and in most cases impossibility of application for their calculation of classical approaches by definition of the basic hydraulic characteristics. On the basis of experimental researches on application in oil systems of diesel locomotives as filters of thin clearing oil and positive results the basic directions of further use and necessity of development of theoretical questions which allow receiving the basic characteristics of these units and dynamics of change of their parameters in operation are certain. The method of modeling and forecasting of a resource of work synthetic filters on the basis of plural regress is offered to model which considers the parametrical dependences received as a result of carrying out of operational tests. Calculations are executed and predicted values of a resource of work of synthetic filters which show in two-rub times an opportunity of increase in run of a diesel locomotive without their replacement are received.
Keywords: : capacity of a dirt, characteristic, diesel locomotive, pollution, regress, resource, synthetic, filter, times